2010
DOI: 10.1159/000320772
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the IL-20 –1723C→G Allele on the 1q Chromosome and Psoriasis Triggered or Exacerbated by an Upper Respiratory Tract Infection in the Chinese Han Population

Abstract: Background: Psoriasis is a cutaneous disorder of multifactorial etiology influenced by both genetic and environmental factors such as infection. Methods: We conducted a genome analysis with 20 microsatellite markers spanning the long arm of chromosome 1 in 36 Chinese families with psoriasis and detected evidence for linkage at 1q21 with a nonparametric linkage score of 1.74, p = 0.03, and 1q32 with one of 1.84, p = 0.03. According to the positional and functional candidate principle, we further investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…In our study, psoriasis was the most common (55%) underlying etiology of pre-existing dermatosis, which was much higher than all the previous reports. As a result, we concluded that there might be a higher frequency of psoriasis or a greater tendency for its generalization in our district [10]; furthermore, unlike in western reports [11], injudicious use of medications, either by the individual or prescribed by physicians, may partly be responsible for the higher rate of psoriasis (the most frequently suspected trigger factors were upper respiratory tract infections and withdrawal of oral medicines including systemic corticosteroids or Chinese traditional herbal medicines). In our study, we also found bullous pemphigoid, hypereosinophilic syndrome and dermatomyositis as causes of erythroderma, which have never or rarely been mentioned in previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, psoriasis was the most common (55%) underlying etiology of pre-existing dermatosis, which was much higher than all the previous reports. As a result, we concluded that there might be a higher frequency of psoriasis or a greater tendency for its generalization in our district [10]; furthermore, unlike in western reports [11], injudicious use of medications, either by the individual or prescribed by physicians, may partly be responsible for the higher rate of psoriasis (the most frequently suspected trigger factors were upper respiratory tract infections and withdrawal of oral medicines including systemic corticosteroids or Chinese traditional herbal medicines). In our study, we also found bullous pemphigoid, hypereosinophilic syndrome and dermatomyositis as causes of erythroderma, which have never or rarely been mentioned in previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…Minor alleles of rs2243188 and rs2243158 in IL19 have a protective effect in patients with the disease (Table 1) [64]. In a case-control study (340 cases and 199 controls), the G allele in rs1713239 ( IL20 ) was associated with psoriasis in a Chinese population (Table 1) [65]. Kingo et al (2004) found an association between G allele carriers of rs2981572 ( IL20 ) and predisposition to psoriasis in Caucasian patients (Table 1) [66].…”
Section: Genetics Of Psoriasismentioning
confidence: 99%
“…Individuals with psoriasis triggered or worsened after upper respiratory tract infections more likely carried interleukin 20 polymorphisms in one study. 36 Another study found that young children with psoriasis more commonly had interleukin 22 promoter variants associated with higher circulating levels of this proinflammatory cytokine important in epithelial host defense. 37 …”
Section: Discussionmentioning
confidence: 99%